CAPITALIZATION ERRORS FOUND IN THE TITLE OF ENGLISH ARTICLES PUBLISHED IN SELECTED JOURNALS - Fitria, Tira Nur (International Journal of Humanity Studies (IJHS), 2024)
In English, a capital letter is used for the first word of a sentence and for all proper nouns (words that name a specific person, place, organization, or thing). This research finds the capitalization errors found in the English titles of journal articles. This research uses descriptive qualitative. The data are Jurnal Akuntansi dan Pajak (JAP) and Jurnal Ilmiah Ekonomi Islam (JIEI). The analysis shows that capitalization errors occurred in English titles, especially in writing prepositions such as in, too, the, and, or, on, of, by, from, for, as, and with. This can occur due to inaccuracy or misunderstanding about the use of prepositions. Writers are usually more concerned with the combination of words in each sentence and the continuity of the writing, the substance of the writing, rather than having to correct capital letters. In English, there is one type of word that basically cannot or should not be placed at the beginning of a sentence, namely determiner/article, prepositions, and conjunctions. Although the capitalization of words in titles might vary depending on the writer's/ author's, institution's, or publication's style, there are certain common capitalization principles to remember. 1) Any title's initial and last words should be capitalized. 2) Using capital letters for nouns and pronouns. Proper nouns are included in this category. 3) capitalizing helpful verbs and "to be" versions. 4) Capitalizing adjectives and adverbs, and 5) capitalizing articles in the title unless they are the first or last word. 6) In titles and short prepositions, do not capitalize short coordinating conjunctions like "and," "but," "or," "for," or "nor." In minimizing mistakes, it is important to know how to write capital letters in the correct title.